Analisis Kinerja Keuangan Bank Umum Syariah di Indonesia berdasarkan Islamicity Performance Index Periode 2015-2019 - Fakhry Hafiyyan Kurniawan; A. Jajang W. Mahri; Rumaisah Azizah Al Adawiyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
Islamic Commercial Banking in Indonesia generally has not fully carry out business activities in accordance with sharia provisions. Therefore, there is a need for a performance measurement tool that is able to express spiritual and social values embodied in Islamic banks. The purpose of this study is to describe the performance of Islamic banking based on Islamicity Performance Index. This research is a quantitative research using descriptive analysis. The data used in this research is secondary data. The study population was Islamic banks in Indonesia during the period 2015-2019, with a sample of twelve banks. Sampling was done by using purposive sampling method. The results showed Panin Dubai Sharia Bank was the best bank in the Profit Sharing Ratio (PSR) indicator. The value of Zakat Performance Ratio (ZPR) in Islamic banking in Indonesia is still low. BNI Sharia is the bank with the highest average value for the ZPR indicator. Equitable Distribution Ratio (EDR) indicates that Mandiri Sharia Bank has the highest average value. Directors-Employees Welfare Ratio (DEWR) shows that BTPN Sharia have fairly high levels of disparity between directors and employees. IIR and IsIR shows that in general Islamic commercial banks in Indonesia have carried out businesss performance in the halal sector. Meanwhile, overall, it received a satisfactory predicate. This research is expected to be taken into consideration for the related institutions to apply the performance measurement of Islamic Commercial Banking in accordance with the concept of Islamicity Performance Index, and be taken into consideration in taking policy measures in accordance with the concept of sharia that will be used in the future.